Ternary ordered alloy catalyst for fuel cell and preparation method of ternary ordered alloy catalyst
By doping lanthanides into the platinum-cobalt binary ordered alloy catalyst to form a ternary ordered alloy catalyst, the problems of poor activity/durability of the existing fuel cell catalyst and lean Pt reserves are solved, and the high activity and stability of the catalyst are achieved, and the performance of the fuel cell is improved.
Patent Information
- Application Number
- CN202411840792.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The carbon-supported Pt nanoparticle catalysts used in existing fuel cells have poor activity/durability in acidic environments and have few reserves of Pt, which leads to high costs and hinders the large-scale production and application of fuel cells.
By doping lanthanides into the platinum-cobalt binary ordered alloy catalyst, a ternary ordered alloy catalyst is formed, which improves the order degree, inhibits the dissolution of metals, and enhances the activity and stability of the catalyst.
The activity and stability of the ternary ordered alloy catalyst is significantly improved, the dissolution of metal is slowed, and the power density and overall performance of the fuel cell are improved.
Smart Images

Figure CN119852425A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to a ternary ordered alloy catalyst for a fuel cell and a preparation method thereof. Background Art
[0002] Oxygen reduction reaction (ORR) is one of the key reactions in proton exchange membrane fuel cells (PEMFCs). As the main cathode reaction, ORR is responsible for reducing oxygen to water or other oxygenates while releasing electrons, which can then be used to generate electricity. Carbon-supported Pt nanoparticle (Pt / C) catalyst is the most widely used cathode catalyst in PEMFCs. However, in the acidic working environment of PEMFCs, Pt nanoparticles are prone to dissolution and migration, resulting in the loss of active sites, making the activity / durability of Pt / C catalysts poor. In addition, the reserves of Pt in the earth's crust are scarce and the price is high, resulting in the cost of Pt / C catalysts accounting for more than 50% of the total fuel cell cost, which hinders the large-scale production and application of PEMFCs.
[0003] In the past decade, alloying Pt with other transition metals (hereinafter referred to as "M") such as Fe, Co, Ni and Cu has reduced the energy of d-orbital electrons and weakened the adsorption strength of oxygen reduction reaction (ORR) intermediates (such as OH*, O*, OOH*, etc.) on the catalyst surface, significantly improving the activity of cathode catalysts and reducing the use of Pt. In the disordered face-centered cubic solid solution structure, M and Pt are randomly distributed, M has poor electrochemical stability, and its activity on the alloy surface is higher than that of Pt, making M more likely to participate in the electrochemical reaction, resulting in easy dissolution of M during actual use, reducing the activity and stability of the catalyst. In the ordered intermetallic structure (such as tetragonal L10 or cubic L12 structure), M and Pt are arranged in a specific stoichiometric ratio and in a highly ordered manner, with strong interatomic interactions, which can greatly slow down the dissolution of M, thereby significantly improving the activity and stability of the catalyst. CN116404182A discloses a low-platinum ternary alloy catalyst and a preparation method thereof, but the synthesis process is complicated and a disordered solid solution alloy is synthesized. During actual use, the metal in the alloy will gradually dissolve, causing serious attenuation of membrane electrode performance.
[0004] Therefore, improving the order of the alloy can significantly slow down the dissolution of the metal, improve the activity and stability of the catalyst, and thus improve the performance of the fuel cell. Summary of the invention
[0005] The purpose of the present invention is to improve the order degree and inhibit the dissolution of metal by doping lanthanide elements into a platinum-cobalt binary ordered alloy catalyst, thereby solving the problem of reduced activity and stability of the catalyst.
[0006] In order to achieve the above object, the present invention provides a method for preparing a ternary ordered alloy catalyst for a fuel cell, the method comprising:
[0007] Step 1, dispersing carbon black in a water-alcohol solution and a surfactant to obtain a carbon black solution;
[0008] Step 2, respectively preparing a platinum precursor solution, a cobalt precursor solution and a lanthanide element precursor solution;
[0009] Step 3, mixing the carbon black solution, platinum precursor solution, cobalt precursor solution and lanthanide precursor solution, introducing reducing gas for thermal reduction, and obtaining a ternary ordered alloy catalyst; the thermal reduction temperature is 700°C-1000°C, and the time is 0.5h-2h.
[0010] Optionally, in step 2, the platinum precursor includes at least one or more of H2PtCl6, K2PtCl4, ammonium chloroplatinate, and platinum acetylacetonate; the cobalt precursor includes at least one or more of cobalt chloride, cobalt nitrate, and cobalt acetate; the lanthanide element precursor is any one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium precursors.
[0011] Optionally, in step 3, the molar ratio of platinum atoms, cobalt atoms and lanthanide atoms is (1-3): (0.25-4): (1-1.5).
[0012] Optionally, in step 1, the volume ratio of water to anhydrous ethanol in the hydroalcoholic solution is (1-2):(1-3), and the mass ratio of the carbon black to the hydroalcoholic solution is (1-2):(1-3).
[0013] Optionally, before step 1, the method further comprises etching the carbon black with sulfuric acid, wherein the mass ratio of the carbon black to the sulfuric acid is (1-1.5):(1-2), and the etching time is 12h-14h.
[0014] Optionally, in step 1, the surfactant includes at least one or more of Triton X-114, Triton X-100, Triton X-45, sodium dodecyl sulfate, and Tween-20.
[0015] Optionally, in step 3, the mixing method comprises ultrasound and stirring, the ultrasound time is 60 min-180 min, and the stirring time is 10 h-15 h.
[0016] Optionally, in step 3, the step further comprises removing the solvent before introducing the reducing gas; the method for removing the solvent is any one of freeze drying, natural air drying, drying, water bath evaporation, rotary evaporation or oil bath evaporation.
[0017] Optionally, in step 3, the reducing gas is any one of a nitrogen-hydrogen mixed gas and an argon-hydrogen mixed gas.
[0018] The present invention also provides a ternary ordered alloy catalyst for a fuel cell obtained by any one of the preparation methods described above.
[0019] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:
[0020] 1) Lanthanide elements are doped into the platinum-cobalt binary ordered alloy catalyst to form a ternary ordered alloy catalyst. Since the atomic radius of lanthanide elements is relatively large, the compressive strain of the platinum-cobalt system is changed, thereby affecting the electronic structure of platinum, cobalt and lanthanide elements, so that the three are arranged in a highly ordered manner, thereby improving the order; the three metal atoms orderly occupy the corresponding lattice points in the lattice, so that more stable chemical bonds are formed between the metals, and the interaction is enhanced, thereby greatly slowing down the dissolution of cobalt and lanthanide elements, which helps to improve the activity and stability of the ternary ordered alloy catalyst.
[0021] 2) Furthermore, using the ternary ordered alloy catalyst as a cathode catalyst of a proton exchange membrane fuel cell can increase the power density of the fuel cell, thereby improving the performance of the fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 TEM image of the ternary ordered alloy catalyst of Example 1 of the present invention; wherein b is a local enlarged image of a.
[0023] Figure 2 1 is the XRD diffraction pattern of the ternary ordered alloy catalyst of Comparative Example 1 and Examples 1-3 of the present invention; wherein b is a partial enlarged view of a.
[0024] Figure 3 These are test curves of oxygen reduction activity of the ternary ordered alloy catalysts of Comparative Example 1 and Examples 1-3 of the present invention; wherein a is a linear voltammetric curve, and b is a cyclic voltammetric curve.
[0025] Figure 4 This is a stability performance test diagram of the ternary ordered alloy catalyst of Example 1 of the present invention.
[0026] Figure 5 This is a power density test graph of the ternary ordered alloy catalysts of Comparative Example 1 and Examples 1-3 of the present invention as cathode catalysts of proton exchange membrane fuel cells. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the description of the present invention, it should be noted that the terms "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0029] As described in the background technology, Pt is alloyed with other transition metals M to form a Pt-M alloy catalyst. In the disordered face-centered cubic solid solution structure, M and Pt are randomly distributed, M has poor electrochemical stability, and its activity on the alloy surface is higher than that of Pt, making M more likely to participate in the electrochemical reaction, which leads to easy dissolution of M during actual use, reducing the activity and stability of the catalyst. In the ordered intermetallic structure, M and Pt are arranged in a specific stoichiometric ratio and in a highly ordered manner, with strong interatomic interactions, which can greatly slow down the dissolution of the metal, thereby significantly improving the activity and stability of the catalyst.
[0030] In order to improve the activity and stability of the catalyst, the present invention dopes lanthanide elements into the platinum-cobalt binary ordered alloy catalyst to form a ternary ordered alloy catalyst. The lanthanide elements can arrange platinum, cobalt and lanthanide elements in a highly ordered manner, thereby improving the order; at the same time, the strong interaction between the ordered metals can greatly slow down the dissolution of cobalt and lanthanide elements, thereby improving the activity and stability of the ternary ordered alloy catalyst. Specifically, the present invention provides a method for preparing a ternary ordered alloy catalyst for a fuel cell, the method comprising:
[0031] Step 1, dispersing carbon black in a water-alcohol solution and a surfactant to obtain a carbon black solution.
[0032] In this step, the mass ratio of carbon black to the aqueous alcohol solution is (1-2): (1-3), and the volume ratio of water to anhydrous ethanol in the aqueous alcohol solution is (1-2): (1-3). The ultrasonic time for dispersing carbon black in the aqueous alcohol solution is 60 min-180 min. After the ultrasonication is completed, a surfactant is added thereto and stirred for 10 h-15 h. After the stirring is completed, the obtained carbon black solution is stirred at a constant temperature of 25 ° C for standby use. Since there is a strong interaction force between carbon black particles, they are easy to agglomerate, which affects the dispersibility. The addition of surfactants can reduce the interaction force between carbon black particles, weaken their agglomeration tendency, and achieve uniform dispersion of carbon black.
[0033] In some embodiments, the surfactant includes at least one or more of Triton X-114, Triton X-100, Triton X-45, sodium dodecyl sulfate, and Tween-20.
[0034] Prior to step 1, the method further comprises etching the carbon black with sulfuric acid, ultrasonically dispersing the carbon black in sulfuric acid, wherein the mass ratio of carbon black to sulfuric acid is (1-1.5): (1-2), and etching in a 60°C oven for 12-14 hours. After etching, the carbon black is centrifuged and washed, and then dried in a vacuum drying oven. The purpose of etching the carbon black with sulfuric acid is to remove other organic impurities and metal ions in the carbon black, thereby improving the purity and quality of the carbon black.
[0035] Step 2: prepare a platinum precursor solution, a cobalt precursor solution and a lanthanide element precursor solution respectively.
[0036] In some embodiments, the platinum precursor includes at least one or more of H2PtCl6, K2PtCl4, ammonium chloroplatinate, and platinum acetylacetonate; the mass of platinum in the platinum precursor is 1%-40% of the mass of the carbon carrier; the cobalt precursor includes at least one or more of cobalt chloride, cobalt nitrate, and cobalt acetate; the lanthanide precursor is any one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium precursors. The molar ratio of platinum atoms, cobalt atoms, and lanthanide atoms is (1-3): (0.25-4): (1-1.5). At this ratio, the order of the ternary ordered alloy can be significantly improved. Platinum precursor solutions, cobalt precursor solutions, and lanthanide precursor solutions of different concentrations can be prepared as needed.
[0037] Step 3, mixing the carbon black solution, platinum precursor solution, cobalt precursor solution and lanthanide precursor solution, introducing reducing gas for thermal reduction, and obtaining a ternary ordered alloy catalyst; the thermal reduction temperature is 700°C-1000°C, and the time is 0.5h-2h.
[0038] After mixing the carbon black solution, platinum precursor solution, cobalt precursor solution and lanthanide element precursor solution, stirring is started for 10h-15h. The purpose of stirring is to make the precursor solution and the carbon black solution mix more completely, which is more conducive to the subsequent loading of the precursor on the carbon black. After the stirring is completed, the solvent is removed and the reducing gas is introduced for thermal reduction.
[0039] In some embodiments, the method for removing the solvent is any one of freeze drying, natural air drying, oven drying, water bath evaporation, rotary evaporation or oil bath evaporation.
[0040] In some embodiments, the reducing gas is any one of nitrogen-hydrogen mixed gas and argon-hydrogen mixed gas. The ternary ordered alloy catalyst obtained by thermal reduction is arranged in a highly ordered manner with a high degree of order; the three metal atoms orderly occupy the corresponding lattice points in the lattice to form a more stable chemical bond between the metals, and the interaction is enhanced, thereby greatly slowing down the dissolution of the metal, and the activity and stability of the ternary ordered alloy catalyst are improved.
[0041] The sulfuric acid, chloroplatinic acid hexahydrate, cobalt nitrate hexahydrate, and cerium nitrate in Comparative Example 1 and Examples 1-3 were all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The preparation method is as follows: 2.72 ml of sulfuric acid (18.4 mol / L) was dissolved in 1 L of water to obtain 0.05 mol / L sulfuric acid, 20 mg of chloroplatinic acid hexahydrate was dissolved in 1 ml of water to obtain 20 mg / ml chloroplatinic acid hexahydrate solution, 20 mg of cobalt nitrate hexahydrate was dissolved in 1 ml of water to obtain 20 mg / ml cobalt nitrate hexahydrate solution, and 10 mg of cerium nitrate was dissolved in 1 ml of water to obtain 10 mg / ml cerium nitrate solution.
[0042] Comparative Example 1
[0043] 30 mg of carbon black was placed in 30 ml of sulfuric acid (0.05 mol / L) for 60 min of ultrasonic treatment, placed in a 60 ° C oven for etching for 12 h, centrifuged and washed, and then placed in a vacuum drying oven for drying. 20 mg of dried carbon black was placed in 20 ml of water-alcohol solution for 60 min of ultrasonic treatment, and then 5 mg of Triton X-114 was added. After magnetic stirring for 10 h, a carbon black solution was obtained. Then 0.734 ml of hexahydrate chloroplatinic acid solution (20 mg / ml) and 0.084 ml of hexahydrate cobalt nitrate solution (20 mg / ml) were added to the carbon black solution in sequence. After magnetic stirring for 12 h, the solvent was removed by rotary evaporation. Finally, it was thermally reduced at 900 ° C in a tubular furnace under argon-hydrogen mixed gas for 2 h, and a binary ordered alloy catalyst was obtained after cooling.
[0044] Example 1
[0045] Place 30 mg of carbon black in 30 ml of sulfuric acid (0.05 mol / L) and ultrasonicate for 60 minutes, place it in a 60°C oven for etching for 12 hours, centrifuge and wash it, and then place it in a vacuum drying oven to dry. Take 20 mg of the dried carbon black and place it in 20 ml of water-alcohol solution for ultrasonication for 60 minutes, then add 5 mg of Triton X-114, and magnetically stir for 10 hours to obtain a carbon black solution. Then, add 0.734 ml of hexahydrate chloroplatinic acid solution (20 mg / ml), 0.084 ml of hexahydrate cobalt nitrate solution (20 mg / ml) and 0.068 ml of cerium nitrate solution (10 mg / ml) to the carbon black solution in sequence, stir magnetically for 12 hours, and use rotary evaporation to remove the solvent. Finally, heat reduce it at 900°C in a tubular furnace under argon-hydrogen mixed gas for 2 hours, and obtain a ternary ordered alloy catalyst after cooling. Figure 1 Shown is a morphology picture of ternary ordered alloy particles.
[0046] Example 2
[0047] The preparation method of the ternary ordered alloy catalyst is the same as that of Example 1, except that the added amounts of the cobalt nitrate hexahydrate solution (20 mg / ml) and the cerium nitrate solution (10 mg / ml) are replaced with 0.269 ml and 0.220 ml.
[0048] Example 3
[0049] The preparation method of the ternary ordered alloy catalyst is the same as that of Example 2, except that the thermal reduction temperature is replaced with 1000°C.
[0050] Figure 2 The XRD diffraction patterns of comparative example 1 and embodiments 1-3 (where b is a local enlarged view of a) are compared with the standard card. The characteristic diffraction peaks of embodiments 1-2 are shifted, indicating that the cerium atom doping is successful. Embodiment 3 shows that at 700°C-1000°C, only changing the thermal reduction temperature does not affect the characteristic diffraction peaks, and the cerium atom doping is successful.
[0051] Example 4
[0052] The oxygen reduction activity of the ternary ordered alloy catalyst was characterized by using an electrochemical workstation with a three-electrode system. The ternary ordered alloy catalyst was used as the working electrode, platinum as the counter electrode, saturated Ag / AgCl as the reference electrode, and the electrolyte was a 0.1M HClO4 solution. The oxygen reduction activity of the catalyst was tested by cyclic voltammetry. In a nitrogen-saturated 0.1M HClO4 solution, the cyclic voltammetry scan was performed in the potential range of +0.05 to +1.00V (compared to the reversible hydrogen electrode) at a scan rate of 50mV s -1 , and the electrochemical active area (e.g. Figure 3 The mass activity and specific activity can be further obtained by linear voltammetry test (as shown in b). Figure 3The intrinsic activity parameters of the catalyst, such as mass activity, specific activity and electrochemical active area, can be calculated by the Koutecky-Levich equation and the platinum loading in the feed. It is calculated that the mass activity of the ternary ordered alloy catalyst of Example 1 is 0.57 A / mg, and the specific activity is 1.18 mA / cm 2 , the electrochemical active area is 48.5m 2 / g; the mass activity of the ternary ordered alloy catalyst of Example 2 is 0.24A / mg, and the specific activity is 0.35mA / cm 2 The electrochemical active area is 68.91m 2 / g; the mass activity of the ternary ordered alloy catalyst of Example 3 is 0.197A / mg, and the specific activity is 0.221mA / cm 2 The electrochemical active area is 89.47 m 2 / g; the mass activity of the binary ordered alloy catalyst in Comparative Example 1 is 0.105A / mg, and the specific activity is 0.035mA / cm 2 The electrochemical active area is 84.67m 2 / g; It shows that when the molar ratio of platinum atoms, cobalt atoms and cerium atoms is appropriate, the ternary ordered alloy catalyst has better mass activity, specific activity and electrochemical active area.
[0053] Example 5
[0054] The stability of the ternary ordered alloy catalyst of Example 1 was characterized by using an electrochemical workstation with a three-electrode system. The ternary ordered alloy catalyst was used as the working electrode, platinum was used as the counter electrode, saturated Ag / AgCl was used as the reference electrode, and the electrolyte was a 0.1M HClO4 solution. The stability of the catalyst was tested by a linear voltammetric curve test. In an oxygen-saturated 0.1M HClO4 solution, a linear voltammetric scan was performed over a potential range of +0.6 to +1.10 V (compared to a reversible hydrogen electrode) at a scan rate of 100 mV s -1 , a total of 20,000 scans. Figure 4 As shown, with the increase of the potential difference, the current density gradually increases, but the difference under different scanning numbers is small, indicating that the ternary ordered alloy catalyst of Example 1 has good stability.
[0055] Example 6
[0056] The power density of the fuel cell was tested by using the ternary ordered alloy catalyst as the cathode catalyst of the low-temperature proton exchange membrane fuel cell. The anode was a 20% Pt / C catalyst, the cathode was a ternary ordered alloy catalyst, and the platinum loadings of the anode and cathode were 0.1 and 0.2 mg / cm 2 , the battery temperature is 60°C, and the back pressure on the anode and cathode sides is 100 kPa. Figure 5 As shown in FIG. 1 , the product of current density and battery voltage is power density. The peak power density of the proton exchange membrane fuel cells of Comparative Example 1 and Examples 1-3 is 631 mW / cm 2 、738mW / cm 2 、646mW / cm 2 、582mW / cm 2 , the power density is not much different, indicating that the ternary ordered alloy catalyst prepared by the method of this embodiment has good application prospects as a cathode catalyst for proton exchange membrane fuel cells.
[0057] In summary, the present invention dopes lanthanide elements into the platinum-cobalt binary ordered alloy catalyst to form a ternary ordered alloy catalyst. The lanthanide elements change the compressive strain of the platinum-cobalt system, thereby affecting the electronic structure of platinum, cobalt and lanthanide elements, so that the three are arranged in a highly ordered manner, and the order is improved; the three metal atoms orderly occupy the corresponding lattice points in the lattice so that a more stable chemical bond is formed between the metals, and the interaction is enhanced, thereby greatly slowing down the dissolution of cobalt and lanthanide elements, which helps to improve the activity and stability of the ternary ordered alloy catalyst. Using the ternary ordered alloy catalyst as a cathode catalyst for a proton exchange membrane fuel cell can improve the power density of the fuel cell, thereby improving the performance of the fuel cell.
[0058] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing a ternary ordered alloy catalyst for a fuel cell, characterized in that: The method includes: Step 1, dispersing carbon black in a water-alcohol solution and a surfactant to obtain a carbon black solution; Step 2, respectively preparing a platinum precursor solution, a cobalt precursor solution and a lanthanide element precursor solution; Step 3, mixing the carbon black solution, the platinum precursor solution, the cobalt precursor solution and the lanthanide element precursor solution, introducing a reducing gas for thermal reduction, and obtaining a ternary ordered alloy catalyst; The temperature of the thermal reduction is 700° C.-1000° C., and the time is 0.5 h-2 h.
2. The method for preparing a ternary ordered alloy catalyst for a fuel cell according to claim 1, characterized in that: In step 2, the platinum precursor includes at least one or more of H2PtCl6, K2PtCl4, ammonium chloroplatinate, and platinum acetylacetonate; the cobalt precursor includes at least one or more of cobalt chloride, cobalt nitrate, and cobalt acetate; the lanthanide element precursor is any one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium precursors.
3. The method for preparing a ternary ordered alloy catalyst for a fuel cell according to claim 1, characterized in that: In step 3, the molar ratio of platinum atoms, cobalt atoms and lanthanide atoms is (1-3): (0.25-4):(1-1.5)。 4. The method for preparing a ternary ordered alloy catalyst for a fuel cell according to claim 1, characterized in that: In step 1, the volume ratio of water to anhydrous ethanol in the hydroalcoholic solution is (1-2):(1-3), and the mass ratio of the carbon black to the hydroalcoholic solution is (1-2):(1-3).
5. The method for preparing a ternary ordered alloy catalyst for a fuel cell according to claim 1, characterized in that: Before step 1, the method further comprises etching the carbon black with sulfuric acid, wherein the mass ratio of the carbon black to the sulfuric acid is (1-1.5):(1-2), and the etching time is 12h-14h.
6. The method for preparing a ternary ordered alloy catalyst for a fuel cell according to claim 1, characterized in that: In the step 1, the surfactant includes at least one or more of Triton X-114, Triton X-100, Triton X-45, sodium dodecyl sulfate, and Tween-20.
7. The method for preparing a ternary ordered alloy catalyst for a fuel cell according to claim 1, characterized in that: In step 3, the mixing method includes ultrasound and stirring, the ultrasound time is 60 min-180 min, and the stirring time is 10 h-15 h.
8. The method for preparing a ternary ordered alloy catalyst for a fuel cell according to claim 1, characterized in that: In the step 3, the solvent is removed before the reducing gas is introduced; the method for removing the solvent is any one of freeze drying, natural air drying, drying, water bath evaporation, rotary evaporation or oil bath evaporation.
9. The method for preparing a ternary ordered alloy catalyst for a fuel cell according to claim 1, characterized in that: In step 3, the reducing gas is any one of a nitrogen-hydrogen mixed gas and an argon-hydrogen mixed gas.
10. A ternary ordered alloy catalyst for a fuel cell obtained according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Low-platinum catalyst, preparation method thereof and application of low-platinum catalyst in fuel cell
CN116404182A
Electrode catalyst for fuel cell, method for producing the same, and fuel cell using the electrode catalyst
CN101682041A
Carbon-supported ordered platinum-cobalt-copper catalyst for fuel cell and preparation method of catalyst
CN109873176A
Carbon-supported platinum alloy powder and preparation method thereof
CN110112430A
High-performance Pt-based three-alloy catalyst and preparation method thereof
CN110635146A